Metasurface-Enabled Microphotonic Biosensors via BIC Modes - Francesco Dell’Olio (Photonics)
Photonic biosensors based on bound states in the continuum (BIC) resonant modes exhibit a transformative potential for high-sensitivity, label-free detection across various diagnostic applications. BIC-enabled metasurfaces, utilizing dielectric, plasmonic, and hybrid structures, achieve ultra-high Q-factors and amplify target molecule interactions on functionalized sensor surfaces. These unique properties result in increased refractive index sensitivity and low detection limits, essential for monitoring biomolecules in clinical diagnostics, environmental analysis, and food safety. Recent advancements in BIC-enabled metasurfaces have demonstrated ultra-low detection limits in the zeptomolar range, making these devices highly promising for real-world applications. This review paper critically discusses the design principles of BIC-based biosensors, emphasizing key factors such as material selection, structural asymmetry, and functionalization strategies that enhance both sensitivity and specificity. Additionally, recent advancements in fabrication techniques that enable precise BIC control with scalable approaches for practical biosensing applications are examined. Case studies demonstrate the effectiveness of BIC metasurfaces for real-time, low-concentration detection, highlighting their versatility and adaptability. Finally, the review discusses future challenges and opportunities, such as integration with microfluidics for point-of-care testing and multiplexed sensing, underscoring the potential of BIC-based platforms to revolutionize the field of biosensing.